Strategy decision making Alpha Company (2015)
"Strategy for US Logistics must be a mix between cost reduction (for post-patent products) and proximity (new business processes must be adopted), regarding this last and principal key driver, one of the potential initiative must be develop an Integrated Supply Chain Management. The policies are essential to build a strong Strategy, to align all activities and actions and to consolidate medium and long vision. Regarding my PMA project, US Logistics Strategy policies are defined as: - Logistics US will be the leader of speed response to the customer making good difference with our competitors. - Logistics network will response to the growth challenge assuring the capacity, Location and capabilities, supporting the sales (USD$525) in 2020 with high efficiency and performance. - ANCLA US will be recognized as a supplier of choice by the key customers, adjusting the OTC Process to accelerate the internal processes. This policies are result of the shared diagnosis process executed in the present document, this effort support clearly the Commercial Strategy view in the Territory US Book and are aligned with the key improve opportunities identified in the diagnosis section " Nota: Para consultar la carta de autorización de publicación de este documento por favor copie y pegue el siguiente enlace en su navegador de internet: http://intellectum.unisabana.edu.co/handle/10818/16833